Length of Stay in a Community Psychiatric Emergency Room: An Analysis of Contributing Factors - Ojimba, M.D., Chiedozie; Ishola, M.D., Adenike; Jegede M.D., Oluwole; Tumenta, M.D., Terence; Adeyemo, M.D., Samuel; Olayinka, M.D., Olaniyi; Maksymenko, M.D., Alexander; Khadka, M.D., Susmita; Shapiro, Andrew; Cherukupally, M.D., Karthik; et al. (International Journal of Innovative Research in Medical Science, 2020)
Background: The length of patients’ stay in the emergency room is a key measure of service delivery and a marker to measure the quality of care. Studies have shown that patients with psychiatric and substance use disorders have a prolonged length of stay in the emergency room compared to medical and surgical patients. Various factors have been found to contribute to this disparity. Method: This is a retrospective case by case review of four hundred and ninety-three consecutive patients who presented to a community psychiatric emergency. Results: Our results show a length of stay ranging between 1.21 – 33.48 hours. The mean length of stay of 8.72 hours and the median was 7.41 hours. Furthermore, the utilization of emergency medication and age above 44 have a significant influence on patients’ length of stay in the psychiatric emergency room (p<0.05). Conclusion: The length of stay in the psychiatric emergency room deserves more study in literature as it remains a metric for service delivery. Although, factors contributing to a prolonged length of stay may vary, in different settings and situations, understanding these factors will improve outcomes for patients in psychiatric emergency rooms.